PENDIDIKAN KARAKTER ANAK DALAM MENINGKATKAN NILAI-NILAI SPIRITUAL - Suharmi Suharmi1 (Jurnal Economic Edu, 2023)
One of negative effects from advance of tecnologycal information is emerging global moral issue including in Indonesia. The effect of this issue could be stated that moral issue of children of Indonesian nation has already happened this time. The solution to solve this issue is through education character. The aim of this education character is to increase education quality which is toward on forms of the children of nation character and good moral. Character increase strategy toward children of nation good moral through three way, namely: 1). Formal education: character education design based class, character education design based school culture, character education based community. 2) Non-formal education: following islamic studies, going to the mosque for taking prayer and gainning additional knowledge. 3) Informal education: family behaviour at home for implementing character values by following our Rusulullah Muhammad Saw and Prophet Luqman ways, parents should be able to become good guidence for their children, pay compliment and give punishment for their children educationally.